Present status of fish diversity in the Beel Kumari in relation to fish sanctuary and fishing gears - Joadder, Md Abdur Razzak; Alam, Md Bayazid; Siddique, Md Abu Bakar; Naim, Jannatun (Journal of Fisheries, 2016)
The study was conducted on Beel Kumari beel (wetland) in Rajshahi, Bangladesh from October 2013 to September 2014. A total of 52 species of fish were recorded and the dominant species was Mystus tengara (Tanagra (9.75%). Exotic species like bighead carp (Aristichthys nobilis), silver carp (Hypophthalmichthys molitrix) and common carp (Cyprinus carpio) were also commonly found. Of the indigenous species, Ompok bimaculatus, Puntius sarana, Pseudeutropius atherinoides, Botia dario, Mystus aor and Chitala chitala were abundant, though these species were rare before the establishment of the fish sanctuary. Four groups of fishing gears i.e. net, trap, spear and harpoons and line fishing were found to use, among them 8 types of net, 7 types of trap, 4 types of spear and harpoon and 4 types of line fishing were recorded. Among these gill net contributed to the highest catch (32%) and push net was the lowest (6%). Most of the respondents (80%) were found to believe that their fish catch had increased considerably due to impact of fish sanctuary establishment and effective community based fisheries management approach employed in this beel.